Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.05.05.079459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sampling bias exaggerates a textbook example of a trophic cascade

Abstract: 1 Understanding how wildland ecosystems respond to the loss and recovery of large 2 predators is vital to decipher the forces that structure food webs and to guide the practice 3 of ecosystem conservation, restoration, and rewilding. This is a major scientific challenge, 4 however, because these large-scale, uncontrolled systems are difficult (or impossible) to 5 sample properly. We show how a tradition of nonrandom sampling has confounded this 6 understanding in a textbook system (Yellowstone National Park) w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Due to the lack of replication and difficulty of isolating trait‐mediated from density‐mediated factors, there is contrasting evidence regarding trait‐mediated trophic cascade effects on communities, ungulate populations, and ungulate physiology. Moreover, recent work highlighted concerns with sampling design that affected the strength of a trophic cascade in the Greater Yellowstone Ecosystem (Brice et al, 2022). Studies on trait‐mediated trophic cascades in particular suffer from the taxonomic and regional biases mentioned previously because they tend to be focused on cursorial predators in the Greater Yellowstone Ecosystem, likely due to the natural experiment provided by the reintroduction of wolves (Bleicher, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of replication and difficulty of isolating trait‐mediated from density‐mediated factors, there is contrasting evidence regarding trait‐mediated trophic cascade effects on communities, ungulate populations, and ungulate physiology. Moreover, recent work highlighted concerns with sampling design that affected the strength of a trophic cascade in the Greater Yellowstone Ecosystem (Brice et al, 2022). Studies on trait‐mediated trophic cascades in particular suffer from the taxonomic and regional biases mentioned previously because they tend to be focused on cursorial predators in the Greater Yellowstone Ecosystem, likely due to the natural experiment provided by the reintroduction of wolves (Bleicher, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In protected areas such as Yellowstone National Park, there is often little to no anthropogenic activity and therefore, the relative importance of wolves to shape the dynamics and functions of an ecosystem is potentially higher (Mech, 1966(Mech, , 2013McLaren and Peterson, 1994;Berger et al, 2001a;Terborgh and Estes, 2010;Kuijper et al, 2016). However, the existence and extent of such effects is still being investigated and questioned (Kauffman et al, 2010;Winnie, 2012;Brice et al, 2020). Outside of protected areas, however, the effects of predators on the density and behavior of the prey populations may be reduced and/or altered due to anthropogenic activities that have a much stronger impact on most trophic levels, from vegetation to herbivores and large predators (Eriksen et al, 2011;Mech, 2012;Kuijper et al, 2016;Gicquel et al, 2020).…”
Section: Browsing Damagementioning
confidence: 99%
“…For example, the reintroduction of wolves to Yellowstone National Park is believed to have reduced both the density of elk (Cervus elaphus canadensis) as well as the browsing intensity on riparian plant communities, which resulted in the recovery of plant species such as quaking aspen (Populus tremuloides) and willow (Salix geyeriana) . Importantly, an increasing number of studies has refuted this idea and provided alternative hypotheses for the observed changes in elk density and plant communities in Yellowstone National Park, such as human harvest and climate, respectively (Vucetich et al, 2005;Creel and Christianson, 2008;Kauffman et al, 2010), as well as sampling bias (Brice et al, 2020). So far, the majority of studies focusing on trophic cascades have been conducted in protected areas with no or little anthropogenic influence, like national parks (Kuijper et al, 2013), however, such dynamics remain to be explored outside of protected areas.…”
Section: Introductionmentioning
confidence: 99%
“…In essence this is a problem with some models used in manuscripts submitted to the Journal of Wildlife Management. Many submitted models rely too much on unverified work of others, make no attempt to obtain information from the animals or their habitat, do not sample randomly, and do not attempt any form of ground truthing, verification, or validation to ensure that data are accurate and results are appropriate for the inferences made, and to justify that a model's intended use meets specified performance requirements (Rykiel 1996, Hastie et al 2001, Roberts et al 2017, Brice et al 2020.…”
mentioning
confidence: 99%
“…Yet fundamental to the reliability of any model is the sampling design that went into guiding model development in the first place (Thompson 1992, Reich 2020). There are dozens of examples of highly sophisticated models built with data collected by an underlying biased sampling design (Brice et al 2020). Too often models are designed to be applied to a single population at a specific time and are not generally applicable (i.e., generality) to broaden knowledge across species or areas (Levins 1966, Wisdom et al 2020.…”
mentioning
confidence: 99%